Gentle Acoustic Crosstalk Cancelation Using the Spectral Division Method and Ambiophonics - Ahrens, Jens; Thomas, Mark; Tashev, Ivan (Proc. IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2013)
We propose the concept of gentle acoustic crosstalk cancellation, which aims at reducing the crosstalk between a loudspeaker and the listener’s contralateral ear instead of eliminating it completely as aggressive methods intend to do. The expected benefit is higher robustness and a tendency to collapse less unpleasantly. The proposed method employs a linear loudspeaker array and exhibits two stages: 1) Use the Spectral Division Method to illuminate the ipsilateral ear using constructive interference of the loudspeaker signals. This approach provides only little channel separation between the listener’s ears at frequencies below approximately 2000 Hz. 2) There we additionally use destructive interference by Recursive Ambiophonics Crosstalk Elimination (RACE). RACE was chosen because of its tendency to collapse gently. In a sample scenario with realistic parameters, the proposed method achieves around 20 dB of channel separation between 700 Hz and 9000 Hz, which appears to be sufficient to achieve full perceived lateralization when only one ear is illuminated.